Anchoring to life: A photovoice study of resiliencies among sexual and gender minority women post-suicide attempt - Shivinder Dhari; John L. Oliffe; Trevor Goodyear; Olivier Ferlatte; Corey McAuliffe; Emily Jenkins (Elsevier, 2023)
Lesbian, bisexual, trans, queer, and other sexual and gender minority (SGM) women are at high risk of suicide. Stigma, discrimination, and exclusion are known risk factors. Contrasting longstanding trends of risk-focused research, this study examines the experiences of SGM women who have attempted suicide focusing on their embodied strengths and resiliencies to continue living post-attempt. Qualitative data from Photovoice methods and in-depth interviews with 11 Canadian-based women who survived a suicide attempt were collected in 2017. Analysis involved an inductive, reflexive thematic approach informed by the minority strengths model. The analysis generated three interconnected themes: 1) reconciling identities and traumas, 2) anchoring to life, and 3) staying afloat: blending professional- and self-help. First, participants described the importance of reconciling past traumas and coming to terms with - and embracing - their SGM identities to live well post-attempt. Second, participants emphasized the potential for community supports to facilitate connectedness, belonging, and a sense of purpose following a suicide attempt. Importantly, this "anchoring" to community also provided a key outlet through which SGM women could process and mitigate experiences of mental health hardship, thereby directly buffering against suicidality. Third, participants underscored that staying afloat post-attempt was a journey requiring persistent and proactive efforts, including use of effective self-management strategies and professional mental-health services. Taken together, these findings offer important insights into the strengths and resiliencies of SGM women who have attempted suicide to guide the efforts of mental health practitioners and the design and evaluation of tailored suicide prevention programs.